An analysis of the effect of heterogeneously distributed inertia constant in generation mix power system by using the graph theory and Dijkstra’s Algorithm - Harshada Nerkar,; Kundu, Prasanta; Chowdhury, Anandita (Penerbit Universiti Kebangsaan Malaysia, 2023)
stability issues. This requires a detailed analysis of the system with an exact share of active power through the generating sources according to nature, location, and control. The interconnected network with a large number of rotating machines at the generation side works coherently with each other. As the share of RES increases, it leads to reduce rotational inertia in the power system. The most important factor affected by inertia is the rate of change of frequency (RoCoF). The higher RoCoF leads the system more vulnerable to small disturbances in the power system. In a large power system network with numerous generating sources and transmission lines, it is difficult to determine the availability of inertia in the system. This paper incorporates the concept of graph theory in the IEEE 30 bus system to analyze the impact of heterogenous inertia distribution on frequency stability. The graph theory network gives the idea about the distance between the nodes and it is helpful to find the share of power from the generating sources. In this paper, we calculate the shortest path between the nodes or substations by using Dijkstra’s algorithm. The betweenness centrality of the node detects the vulnerable nodes in the system from the frequency response point of view.